Políticas públicas de saúde, risco e vulnerabilidade em AIDS: discursos e ações voltadas às travestis no município de Franca/SP - Santos, Elaine Teixeira Alves dos [UNIFESP] (2014)
The incidence of AIDS among men who have sex with men experienced a significant increase in recent years in Brazil and among the most vulnerable groups are the transvestites and transsexuals. We hypothesized that, despite a policy of prevention and health promotion aimed at transvestites and transsexuals, there is a difficulty of ensuring access to these policies in fact, with the backdrop of the issue of AIDS is still doing this in reality of this population. We use a qualitative approach to the research. Data collection occurred through the techniques of research documents related to public policy and build narratives of four users of the Center for STD Prevention of Franca. Inclusion criteria were that subjects attend the Center for Prevention, which had aged 18 years and who agreed to participate in the research. The subjects were chosen with the aid of the unit staff, noting the inclusion criteria. We organize the data using the technique of triangulation method that allows the combination and cross data extracted from the narrative, the documentary research and field diary. The analysis was conducted in the light of the hermeneutic-dialectic perspective. The analysis was performed on three foundational principles: 1 - From risk to vulnerability AIDS: changes in discourse and maintenance practices; 2 - Disease Prevention and Health Promotion; 3 (In) visibility, prejudice and discrimination: developments in the health-disease process. Through research it was possible to understand that transvestites and transsexuals still have their health demands mainly related to the issue of AIDS, another important finding is the fact that this population be accessing the health facilities of the city, but only do so when they are in a disease process, ie, with attention to transvestites and transsexuals are focused on curative interventions.